The Body as Is: The Copula of the (Cinematic) Body - Fuery, Patrick (Signs - International Journal of Semiotics, 2008)
This paper examines the body in cinema as a type of copula between the narrative of the film and the act of spectating. The cinematic body is seen as a type of hinge between what is represented (with its narrative force) and the processes of becoming a spectator of a film. Part of the analysis involves a comparison between the semiotic and philosophical ideas of CS Peirce with the works of Freud and Lacan. The paper examines how we might use a combination of these theories to compose a new theory of the cinematic body. Examples are drawn from the films of Malick, and Lynch, and the paper concludes with some of the implications of Bergson and Deleuze for these issues.